Mental health and social problems : a social work perspective - Heller, Nina Rovinelli; Gitterman, Alex (Routledge, 2011)
"Mental Health and Social Problems is a textbook for social work students and practitioners. It explores the complicated relationship between mental conditions and societal issues as well as examining risk and protective factors for the prevalence, course, adaptation to and recovery from mental illness. The introductory chapter presents bio-psycho-social and life-modeled approaches to helping individuals and families with mental illness. The book is divided into two parts. Part I addresses specific social problems, such as poverty, oppression, racism, war, violence, and homelessness, identifying the factors which contribute to vulnerabilities and risks for the development of mental health problems, including the barriers to accessing quality services. Part II presents the most current empirical findings and practice knowledge about prevalence, diagnosis, assessment, and intervention options for a range of common mental health problems - including personality conditions, eating conditions and affective conditions. Focusing throughout upon mental health issues for children, adolescents, adults and older adults, each chapter includes case studies and web resources. This practical book is ideal for social work students who specialize in mental health"--Provided by publisher.